2020
DOI: 10.1111/age.12994
|View full text |Cite
|
Sign up to set email alerts
|

Ear type in sheep is associated with the MSRB3 locus

Abstract: Ear morphology is an important determinant of sheep breeds. It includes different variable traits such as ear size and erectness, suggesting a polygenic architecture. Here, we performed a comprehensive genome-wide analysis to identify regions under selection for ear morphology in 515 sheep from 17 breeds fixed for diverse ear phenotypes using 34k SNP genotyping data. GWASs for two ear type traits, size and erectness, revealed a single genome-wide significant association on ovine chromosome 3. The derived marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
(52 reference statements)
0
12
0
Order By: Relevance
“…for its association with large and/or floppy ear type in sheep using a population‐based approach (Paris et al . 2020). MSRB3 has also been shown to regulate ear size in pigs (Zhang et al .…”
Section: Discussionmentioning
confidence: 99%
“…for its association with large and/or floppy ear type in sheep using a population‐based approach (Paris et al . 2020). MSRB3 has also been shown to regulate ear size in pigs (Zhang et al .…”
Section: Discussionmentioning
confidence: 99%
“…It was found in selection signatures in local breeds of sheep (de Simoni Gouveia et al, 2017;Signer-Hasler et al, 2019) and cattle (Bertolini et al, 2020;Suezawa et al, 2021). Interestingly, the abovementioned MSRB3 gene, found in the ROH island detected on OAR3, has been also associated with the ear type (Paris et al, 2020). Another is the CHCHD7 that was found in selection signatures in cattle and sheep (Randhaw et al, 2014;Zhao et al, 2015).…”
Section: Genes Located In the Roh Islandsmentioning
confidence: 98%
“…RXFP2 was strongly associated with sheep horn morphology (Johnston, et al 2011; Kijas, et al 2012), and SUPT3H was reported to be associated with nose bridge breadth(Adhikari, et al 2015), nose morphology(Claes, et al 2018), chin dimples(Pickrell, et al 2016) and forehead protrusion (Bonfante, et al 2021). MSRB3 had been identified as a candidate gene for external ear morphology in pig, dog, goat and sheep (Boyko, et al 2010; Webster, et al 2015; Wei, et al 2015; Zhang, et al 2016; Zhang, et al 2017; Chen, et al 2018a; Kumar, et al 2018; Paris, et al 2020). Furthermore, several other genes (e.g., STXBP5L, DENND1A, VPS13B ) were identified in GWAS studies of human facial shape analyses (Claes, et al 2018; Bonfante, et al 2021; White, et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…S14 ). Interestingly, ear morphology has been mapped to MSRB3 in sheep using breeds fixed for divergent ear types (Paris et al, 2020), designated as ear size (large-eared vs. small-eared) and ear erectness (drop-eared vs. prick-eared). This gene yielded significant f d values in 9 pairwise comparisons of argali vs. domestic population, encompassing chr3:154,000,001-154,090,000 ( Fig.…”
Section: Resultsmentioning
confidence: 99%